The role of benzotriazole modified zinc phosphate in preventing corrosion-driven organic coating disbondment on galvanised steel. (September 2020) - Wint, N.; Griffiths, C.M.; Richards, C.J.; Williams, G.; McMurray, H.N.
Highlights: Investigation of cathodic delamination of PVB from hot dip galvanized steel. Production of corrosion inhibitor whereby BTA adsorbed onto zinc phosphate. Comparison of the ability of ZnPhos-BTA and ZnPhos to resist coating delamination. pH dependent release of BTA from ZnPhos in presence of NaCl. Reduced cathodic delamination rate in presence of ZnPhos-BTA compared to ZnPhos. Abstract: A simple modification using adsorbed benzotriazole is shown to significantly improve the performance of zinc phosphate corrosion inhibitive pigment in slowing rates of organic coating failure. The novel inhibitor, ZnPhos-BTA, is dispersed within a model coating and the scanning Kelvin probe (SKP) is used to monitor corrosion driven cathodic coating delamination from hot dip galvanized steel (HDG). Disbondment kinetics are obtained as a function of pigment volume fraction ( ϕ ) and compared to those obtained for unmodified ZnPhos. Additions of 0.1 ϕ ZnPhos-BTA result in an almost 20-fold reduction in delamination rate compared to standard ZnPhos at the equivalent volume fraction.